Incidencia de la ejecución de Auditoría Financiera en la gestión operativa de la empresa agroindustrial Laredo S.A.A. año 2015 - Guzmán Alfaro, Alexis Iván (2017)
The present investigation, denominated: "INCIDENCE OF THE EXECUTION OF FINANCIAL AUDIT IN THE OPERATIONAL MANAGEMENT OF THE AGROINDUSTRIAL COMPANY LAREDO S.A.A. IN THE YEAR 2015". Therefore, the purpose of the work is that the financial audit focuses on its application in operational management and how it should contribute to a better performance and objectives in the company, as well as improving the use of resources, using current law regulations, and giving opportunities for improvement for an optimal growth in each of the enterprise’s areas, being reflected in the results of the financial statements at the end of the period. In this research the descriptive method will mainly be used, which will be complemented with statistical, deductive and inductive analysis, among others. The population is made up of the officials, managers of areas and personnel of the Agroindustrial Company Laredo S.A.A. The main techniques used in the research are: . Interview . Surveys . Documentary analysis. The main instruments that we will use with these techniques are: . Interview’s guides, . Questionnaire . Documentary analysis guides